Ouvrages apologétiques Exhortation aux grecs (Marcel d'Ancyre ?); Discours aux grecs; Sur la monarchie. - Bost-Pouderon, Cécile.; Justinus Martyr philosophus; Pierre, Marie-Joseph; Pilard, Pierre; Pouderon, Bernard, 1951- (Paris Cerf, 2009)
Three 'Apologies' composed somewhere in the third century A.D., once attributed to Justin Martyr, and erroneously included in the 'Corpus Iustini.'
Exhortation aux grecs / (Marcel d'Ancyre?) -- Discours aux grecs -- Sur la monarchie.
Includes bibliographical references (p. 9-26).
Introduction en français. Texte en grecque ancien et français. Discours aux grecs en français, grecque ancien et syriaque.
Keywords: Apologetics -- Early works to 1800.; Apologetics -- History -- Early church, ca. 30-600; Christian literature, Early -- Greek authors; Christian literature, Early -- Greek authors -- Translations into French; Theology; 239.3 -- Apologetica: tegen de heidenen